Studi Adsorpsi Sianida dari Tailings Pengolahan Emas dengan Metode Resin-In-Pulp - Ninik Lintang E.W.; Cut Shafira; Palguno Helyoso (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Cyanidation is an efficient and inexpensive gold extracting process from ore, allowing gold recovery from low-grade ore carried out economically. The disadvantage of cyanidation process is the generation of highly toxic cyanide-containing tailings. Such tailings need to be treated prior to disposal, in order to comply with environmental requirements. There are two methods to overcome cyanide-containing tailing, by recycling and recovery. Cyanide recovery will eliminate the cyanide destruction cost and will reduce fresh cyanide purchasing cost. Cyanide adsorption (as part of Hannah Process) has been studied using batch adsorption techniques, to examine the contact time, adsorbent dose, and maximum adsorption capacity of Lewatit U-SO4 resin for cyanide removal. Results revealed that adsorption rate initially increased rapidly, and the optimum removal efficiency was reached within two hours. Further increase in contact time did not show significant change in equilibrium concentration; that means, the adsorption has reached equilibrium. The adsorption isotherms could be fitted well by the Langmuir model. The  RLvalue in the investigation was less than one, indicating that the adsorption of cyanide onto the  resin is favorable. The resin optimum dose was 44 g/L and  the maximum capacity was20 mg CN/g resin, equivalent to 0.846eq/L resin.